ADOPTION OF AI IN FINANCIAL AUDITING AN EMPIRICAL ANALYSIS USING THE TECHNOLOGY ACCEPTANCE MODEL (TAM) - Rohmah, Aida; Bangsawan, Lakasamana; Susanto, Ferry (Institut Bakti Nusantara, 2025)
The development of artificial intelligence technology has significantly transformed financial auditing practices, particularly in terms of efficiency, accuracy, and fraud detection capabilities. This study aims to analyze the role of artificial intelligence in financial audits, identify opportunities and challenges for the accounting profession, and propose strategic recommendations for competency enhancement. The research employed a mixed method approach, combining qualitative analysis through in-depth interviews, case studies, and focus group discussions, with quantitative analysis from an online survey involving 120 auditors and accountants. The findings reveal that approximately half of the respondents have adopted artificial intelligence in auditing, with the main benefits being improved accuracy, efficiency, and fraud detection. Nevertheless, major challenges remain, including limited human resource capacity, algorithmic bias risks, and inadequate regulations. A competency gap analysis indicates that individual understanding of artificial intelligence is relatively higher than organizational readiness, highlighting the need for stronger institutional support. These results emphasize that digital transformation in auditing requires an integrated strategy combining enhanced technological literacy among auditors, adequate infrastructure provision, and the development of AI based auditing regulations. Accordingly, this study provides an important contribution to advancing the accounting profession in adapting to the digital era.